2021
DOI: 10.3389/fendo.2021.624309
|View full text |Cite
|
Sign up to set email alerts
|

SNAPIN Regulates Cell Cycle Progression to Promote Pancreatic β Cell Growth

Abstract: In diabetes mellitus, death of β cell in the pancreas occurs throughout the development of the disease, with loss of insulin production. The maintenance of β cell number is essential to maintaining normoglycemia. SNAPIN has been found to regulate insulin secretion, but whether it induces β cell proliferation remains to be elucidated. This study aimed to explore the physiological roles of SNAPIN in β cell proliferation. SNAPIN expression increases with the age of mice and SNAPIN is down-regulated in diabetes. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…[ 39 , 40 ] Studies have found that CCND1 plays a role in obesity-related T2DM, which is related to its participation in fatty acid and glucose metabolic pathways and oxidation/reduction reactions [ 41 ] ; while CDK4/6 has a regulatory effect on human beta cell proliferation. [ 42 ] Studies have found that CDK1 is the key to drive oxidative phosphorylation, and the abnormal increase in the secretion of oxidative phosphorylation components may be the basis for the development of diabetes. [ 43 ] In the pathogenesis of T2DM, the increase or decrease of the above targets plays an important role in the occurrence, development and treatment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 , 40 ] Studies have found that CCND1 plays a role in obesity-related T2DM, which is related to its participation in fatty acid and glucose metabolic pathways and oxidation/reduction reactions [ 41 ] ; while CDK4/6 has a regulatory effect on human beta cell proliferation. [ 42 ] Studies have found that CDK1 is the key to drive oxidative phosphorylation, and the abnormal increase in the secretion of oxidative phosphorylation components may be the basis for the development of diabetes. [ 43 ] In the pathogenesis of T2DM, the increase or decrease of the above targets plays an important role in the occurrence, development and treatment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…After transfection for two days, the UA+IRS2 group was treated with 15 mg/dL of UA for 24 h, and then the cells were subjected to IP as mentioned above. LC-MS analysis was executed according to our previously described method ( 32 ). The peptides were desalted by StageTips ( 33 , 34 ).…”
Section: Methodsmentioning
confidence: 99%